A Systematical Comparison of Catalytic Behavior of NM/γ-Al2O3 (NM = Ru, Rh, Pt, Pd, Au, Ir) on 1,2-Dichloroethane Oxidation: Distributions of By-Products and Reaction Mechanism - Lu Li; Jingjie Zhang; Han Xu; Mingjiao Tian; Chi He (Applied Sciences, 2022)
Understanding the reaction path and mechanism of chlorinated volatile organic compound (CVOC) destruction is important for designing efficient catalysts, especially for the application of noble metal-based materials. Herein, several typical noble metals, Ru, Rh, Pt, Pd, Au, and Ir, supported on γ-Al2O3 catalysts were synthesized by the hydrazine hydrate reduction method for 1,2-dichloroethane (1,2-DCE) elimination. Various character measurements were conducted, and the results suggest that the high-valence state of noble metals is beneficial for the 1,2-DCE reaction as it enables the enhancement of the mobility of the surficial active oxygen species of catalysts. Among the noble metals, Ru/γ-Al2O3 expresses superior catalytic reactivity, with a 90% pollutant conversion rate at 337 °C, and competitive CO2 selectivity, 99.15% at the temperature of total oxidation. The distribution of by-products and the degradation routes were analyzed online by GC-ECD and in situ diffuse reflectance infrared spectroscopy, which may provide helpful insight for the future application of noble metal-based catalysts for CVOC elimination in industrial fields.